Pelatihan Pembuatan Packaging dalam Upaya Peningkatan Produk - Asdilvira, Bebi (Jurnal Pengabdian Masyarakat Inovasi, 2024)
The household-scale food industry in Medan City has great potential but is often constrained by the low visual competitiveness of its products. The main problem faced is the use of conventional packaging which is minimal in information and unattractive, making it difficult to compete in the modern market. This community service activity aims to improve the knowledge and skills of "Sate Pisang Keju" (Cheese Banana Satay) business actors through training in innovative packaging and label design. The implementation method used includes educational lectures on the strategic functions of packaging as well as participatory workshops (direct practice) starting from the design stage to precise labeling techniques. The results of the activity show a significant increase in the participants' competence in understanding the concepts of branding, brands, and packaging aesthetics. Visually, there was a transformation of the product from plain plastic mica packaging to packaging equipped with informative sticker labels with ergonomic positions. This change directly increases the perceived quality and selling value of the product in the eyes of consumers. The conclusion of this program confirms that simple but effective packaging technology intervention is able to change the image of local products to be more professional. The implication of this activity is the need to expand similar programs for other MSME actors in Medan City to accelerate creative economic growth based on local wisdom.